Adaptive Tracking Control of Uncertain Robotic Manipulators - Zhang, Mingxu; Zhang, Zhengqiang; Sun, Meimei (IEEE transactions on circuits and systems. II, Express briefs, 2024)
This brief focuses on the tracking control problem of robotic manipulators subject to the uncertainties in both kinematics and dynamics. We use the zeroing-dynamics method to address uncertain kinematics. By adjusting the unknown Jacobian matrix of the kinematics in real-time, we can resolve the uncertain kinematics. An observer-based estimation law is constructed to ensure that the estimation error satisfies global exponential stability, to exactly estimate uncertain dynamics, and to solve disturbance problems of unknown dynamics. This brief establishes the theoretical framework of tracking control, it has been theoretically shown that integrated control system has global exponential stability and can achieve tracking control of the end effector. The presented control method can better assure tracking control performance and has stronger robustness to uncertain kinematics and dynamics. Finally, we validate the validity of the theoretical results through simulation research.